HUMANISTIC VALUES IN ENGLISH ELECTRONIC SCHOOL TEXTBOOK FOR SENIOR HIGH SCHOOL - IstiÃ¢Â€Â™anah, Arina (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2015)
The English electronic school textbooks or known as BSE (Buku Sekolah Elektronik) for senior high school are used by students in Indonesia since this kind of book is downloadable free in the internet. Due to that reason, this study intends to evaluate the language use in the book by means of appraisal analysis. The focus of attention will be on the representation of humanistic values in the book. The values are necessarily to promote due to the fact that textbooks become one of resources for students to build their characters as language enables humans to express their conscious awareness of emotions (Dong, 2006). Consequently, what the book presents influences the studentsâ attitudes towards certain issues. This research attempts to find out what humanistic values are promoted in the book and how the writersâ attitudes are represented to show the humanistic values.The analysis shows that the book presents three values: respecting others, nature and social issues. The writersâ attitudes towards the values are dominated by affect: 87% in respecting other people and 73% in respecting social issues. To respect nature, the writersâ attitudes are shown in appreciation, presented in 71%.